Impact of COVID-19 on Stock Market Volatility and Forecast using ARIMA and EGARCH (Global Journal of Human-Social Science, 2023)
Abstract not found
Keywords: covid-19; stock exchange; composite index; autoregressive; moving average; ARIMA; GARCH